Evaluation of debonding in CFRP-epoxy adhesive single-lap joints using eddy current pulse-compression thermography. (1st December 2019) - Yi, Q.; Tian, G.Y.; Yilmaz, B.; Malekmohammadi, H.; Laureti, S.; Ricci, M.; Jasiuniene, E.
Abstract: Contaminations arising during the manufacturing or usage of Carbon Fiber Reinforced Plastic (CFRP)-epoxy adhesive single-lap joints can drastically affect the mechanical performance of the structure and eventually lead to its catastrophic failure. Eddy current stimulated thermography has been recently proposed for detecting and characterizing defects in composite materials. The characterization of debonding in adhesive single-lap joints in composites by eddy current stimulated thermography can be challenging due to the anisotropic thermal diffusion caused by the anisotropic conductivity and multi-layer nature of the composites. This work tackles the challenge of detecting the interface contamination by combining eddy current pulse-compression thermography and image post-processing algorithms. The impulse responses from samples containing either brass, release film or release agent contaminations obtained through pulse-compression combined with Eddy Current Pulsed Thermography (ECPT). Non-uniform heating patterns are removed by partial least square technique. Then, the time instants containing meaningful information about the contaminated interface layer are inferred by comparing each norm of kernel principal component over suitable time windows. The evaluation of contamination depths and properties are conducted in selected time windows by principal component analysis and time-phase analysis. Results proved that release agent contamination plays the minor role in changing the electrical and thermal properties of the single-lap joints compared with brass and release film.